Application of hill's strategy development framework on fast food restaurant business in Brunei Darussalam - Ringim, Kabiru Jinjiri; Kura, Kabiru Maitama; Ibrahim, Fahmi (Universiti Utara Malaysia Press, 2019)
A strategy development framework that based on integrated working partnership is gearing towards meeting customer needs. It consists of defining corporate objectives, developing marketing strategies to achieve these goals, assessing how different products win orders, establishing the most appropriate means to manufacture, and providing the necessary manufacturing infrastructure. There are various frameworks and approaches used in the analysis of a company’s strategic position. One of the most straightforward is the SWOT analysis; SWOT is an acronym for “strengths, weaknesses, opportunities, and threats.” Nevertheless, the research of the usage of such a tool is comparatively rare. Fast Food Restaurant Business is restaurant chain and international franchise. It has over 15,000 locations worldwide as of 2015. It is not only a restaurant business but also does delivery services. It is known for its Italian-American cuisine menu including pizza and pasta, as well as side dishes and desserts. It has diversification of product especially in their pizza, for example, different country has a varied menu with a unique local taste. In Brunei, its signature Fast would be Honey Garlic Chicken and Tuna Delight. These two pizzas are favorite as it has been on their menu for over a decade. Fast Food Restaurant Business in Brunei Darussalam started its operation in over two decades, under a Registered Local Corporation (RLC). RLC handle two brands of Fast Food Restaurant Business. Currently, Fast Food Restaurant Business Brunei has branches nationwide, including three (3) Primo Fast Food Restaurant Business. The primary objective of Fast Food Restaurant Business Brunei is to be the number one favorite fast food restaurant brand in Brunei, and other purposes discussed in following a section of Table 1; the application of the Hill’s Strategy Development Framework.